Perancangan Aplikasi Web Penyewaan Lapangan Futsal (Studi Kasus :Sumber Jaya Futsal Tangerang) - Ika Yuniva; Andriansah Andriansah; Yoga Nur Ikhsan (Bianglala Informatika, 2020)
Futsal sports have developed and are popular in Indonesia. Sumber Jaya Futsal is one of the providers of futsal field rental business in Tangerang. Sumber Jaya Futsal currently does not have a web-based system, the system for leasing futsal fields in Sumber Jaya Futsal is still conventional, where customers come directly or by calling to find out the schedule of available futsal fields. The rental transaction scheduling and report system is still using a notebook. Based on the problem, the purpose of this research is to produce a draft web application for futsal field rental at Sumber Jaya Futsal Tangerang. In this study to collect data the author uses case studies with methods of observation and literature. The design of this web application is made using the PHP programming language, assisted by xampp as a web server, MySQL for database management, ERD (Entity Relationship Diagram) and LRS (Logical Record Structure) to describe the data model. While the author's software development method uses the Waterfall Method.